Os efeitos do parcelamento espontâneo do ICMS na arrecadação do estado do Ceará, no período de 2018 a junho de 2024 - Ribeiro, Régia Thays Marques de Melo (2025)
This dissertation analyzes the effects of spontaneous installment programs (parcelamento espontâneo) of the ICMS tax on the State of Ceará’s revenue between 2018 and 2024. The ICMS, which accounts for more than 80% of the state’s own tax revenue, is essential for financing public policies. The study highlights installment programs as an instrument provided for in the National Tax Code (CTN) and regulated in Ceará by Decree No. 33,327/2019, which allows taxpayers to voluntarily regularize tax debts, thus encouraging fiscal compliance. Based on data from the Ceará State Treasury Department (SEFAZ-CE), the analysis considered the number of installment agreements, payment terms, and amounts actually paid, focusing only on the ICMS principal. To measure the effects on revenue, Vector Autoregressive (VAR) models were applied. The results indicate no statistically significant impact of spontaneous installment programs on the average ICMS revenue, when analyzing the entire sample. However, there is weak evidence of a possible positive effect on the unexpected increase in revenue collections between March and June 2024. It is concluded that spontaneous installment programs strengthen fiscal predictability and voluntary compliance, although their long-term structural effects require caution.